Evidence of porcine circovirus type 2 and co-infection with ungulate protoparvovirus 1 (porcine parvovirus) in mummies and stillborn piglets in subclinically infected farm - Serena, Maria Soledad; Dibarbora, Marina; Olivera, Valeria Soledad; Metz, German Ernesto; Aspitia, Carolina Gabriela; Pereda, Ariel Julian; Echeverria, Maria Gabriela; Cappuccio, Javier Alejandro (Elsevier, 2021)
Porcine circovirus type 2 (PCV2) and protoparvovirus 1 (PPV) were detected as single infection (6/131) and (11/131) respectively, or co-infection (6/131) in fetuses and stillborn piglets from normal deliveries in a farm without reproductive problems. Twenty in twenty-three positive samples were over 70 days of gestation, which is when the fetus becomes immunocompetent, and the presence of a NADL-2 PPV strain suggests fetal immune system impairment. Phylogenetic analysis of sequences obtained showed that 8/9 sequences are related to cluster 13 and the remaining is grouped into cluster 11 sequences. An increase in variability in ORF2 sequences in Argentina was observed. It is not clear whether the detection of fetuses positive to PPV and PCV2 is of epidemiological importance in a subclinically affected farm. However, the results of this study showed that currently used vaccines and vaccine protocols do not fully protect against PPV or PCV2 fetus infection.